Improving the Quality of Laser-Welded Butt Joints of Metal–Polymer Sandwich Composites - Serguei P. Murzin; Heinz Palkowski; Alexey A. Melnikov; Maksim V. Blokhin; Stanislav Osipov (Applied Sciences, 2022)
Sandwich panels are promising composite materials, although the possibilities for their thermal joining are limited due to the degradation of the polymer core at elevated temperatures. The purpose of this study is to improve the quality of the butt joints in metal–polymer sandwich composites performed by laser welding. A pulsed Nd:YAG Rofin StarWeld Performance laser was used to perform the two-sided welding of the metal–polymer three-layer composite material. On each of the two sides of the material, a welded joint was made with partial penetration of the covering steel sheets, which was considered a prerequisite for preventing the degradation of the core polymer layer. The energy density of the laser irradiation was redistributed by increasing the diameter of the laser spot. The structure of the welded joints was examined using a polarized optical microscope and a scanning electron microscope. It was determined that the laser treatment resulted in a partial penetration weld on each of the two covering metal sheets of the material, reaching a depth of more than 50% of the sheet’s thickness without damaging the polymer. The welding area consisted of two zones, one being the weld metal and the other the heat-affected zone. As a result of relatively rapid heating and cooling cycles, fine-dispersed structures were formed in the heat-affected and remelted zones. The performed tensile tests showed that the strength of the welded area was about 80% of that of the base material.